Governance matters - Kaufmann, Daniel 1951-; Kraay, Aart.; Zoido-Lobaton, Pablo; World Bank. (Washington, DC World Bank, 1999)
Six new aggregate measures capturing various dimensions of governance provide new evidence of a strong causal relationship from better governance to better development outcomes.
Keywords: Public administration; Political stability; Rule of law; Political corruption; Political indicators; Economic development